Experimental and ab-initio study of the Zr- and Cr-enriched aluminide layer produced on an IN 713C Inconel substrate by CVD; investigations of the layer morphology, structural stability, mechanical properties, and corrosion resistance. (July 2016) - Sitek, R.; Kwaśniak, P.; Sopicka-Lizer, M.; Borysiuk, J.; Kamiński, J.; Mizera, J.; Kurzydłowski, K.J.
Abstract: The paper discusses the effect of zirconium and chromium on the microstructure and properties of the aluminide layers produced on an Inconel 713C nickel superalloy substrate. The aluminizing process was conducted using the chemical vapor deposition (CVD) method in AlCl3 + ZrCl3 vapors and a hydrogen atmosphere as the carrier gas. This low-activity aluminizing process yielded a diffusive multi-component aluminide layer composed of three main zones: the outer zone, about 3 μm thick, chiefly built of AlNi2 Zr, Ni3 Zr and Al3 Zr4, the intermediate zone, about 6 μm thick, containing the β-NiAl phase, and the inner zone, with a thickness of about 7 μm, mostly composed of the Cr2 Al and β-NiAl grains. The substrate contained semi-coherent γ′-phases (Ni3 Al) separated from the γ-austenite matrix by a dislocation net. DFT calculations have shown that Cr added to β-NiAl markedly increases the elastic constant C11 and the isotropic shear modulus G, whereas the addition of Zr decreases the C44 component. Moreover, zirconium added to β-NiAl increases its plasticity thanks to the formation of wide-spread metallic ZrNi bonds. It has been found that the Zr + Cr-modified aluminide layer formed on the Inconel 713C nickel superalloy improves its corrosion resistance (as measured in a 0.1 M Na2 SO4 solution). Highlights: The NiAlZr layers were produced by CVD method. The NiAlZr layers improve corrosion resistance of the IN 713C exposed in a 0.1 M Na2 SO4 solution. An addition of Cr to the NiAl phase increases the elastic constant C11 and the isotropic shear modulus G. The addition of Zr to the NiAl structure increases its plasticity due to the formation of wide-spread metallic ZrNi bonds.